Bibliometric assessment of world scholars’ international publications related to conceptual metaphor - Han, Ying; Peng, Zhibin; Chen, Hong (Frontiers in Psychology, 2022)
Research on metaphor has gained increasing attention of world’s scholars since the publication of Lakoff and Johnson’s collaborated book Metaphors We Live By in 1980. The present study comprises a pioneering review of publications on Conceptual Metaphor Theory (CMT) and provides a clear overview of international research in relation to CMT. In total, 4458 bibliometric recordings ranging from 1980 to 2022 were collected from the Web of Science (WOS) Core Collection. The descriptive analysis presents the trend of annual publications, the top journals and the top authors in the number of published articles. A document co-citation analysis was conducted via CiteSpace to navigate the key documents in this field. A visualization of keywords and its cluster analysis were conducted to show the research fields and dominant topics. The top 5 high-frequency keywords were language, comprehension, conceptual metaphor, discourse, and figurative language. The most prominent 5 clusters are labeled as right hemisphere, self, time, teacher education, and corpus linguistics. The present review through CiteSpace flags the need for more investigations of CMT from more aspects or interdisciplinary studies, such as metaphor translation, metaphor in literature, metaphor and corpus linguistics, etc.